English vakrokti jivita sangraha. - KRISHNAMURTHY (Shikaripura) (Mangalore Akhila Karnataka Samskrata Parishad, 1995)
A Brief Summary of Kuntaka's Vakroktijivita rendered in to English by Dr.Shikaripura Krishnamurthy, HoD of Sanskrit, St Aloysius College